FINANCIAL ACCOUNTING - ARORA R K (NEW DELHI WILEY INDIA PVT. LTD, 2025)
"Financial Accounting: Fundamentals, Analysis and Reporting," authored by R.K. Arora, is a textbook designed to provide a thorough understanding of the principles and practices of financial accounting. Published by Wiley India, the book is currently in its 2nd edition. It caters primarily to students of business and management, aiming to equip them with the essential knowledge required to understand and interpret financial statements.
FINANCE
BBA & MBA
Keywords: ACCOUNTING; MANAGEMENT